Clinical characteristics and variant analyses of transient infantile hypertriglyceridemia related to GPD1 gene - Wang, Jun; Sun, Xinrong; Jiao, Lianying; Xiao, Zhengtao; Riaz, Farooq; Zhang, Yufeng; Xu, Pengfei; Liu, Ruiqing; Tang, Tiantian; Liu, Meiqi; Li, Dongmin (Frontiers in Genetics, 2022)
Objective: Our study aims to summarize and analyze the clinical characteristics of HTGTI, variants in the GPD1 gene, and the effect of HTGTI on the protein structure of GPD1. Methods: Retrospective analysis, using the general data, symptoms, signs and auxiliary examinations, was performed on the patients with HTGTI which were confirmed by genetic testing in our hospital and reported cases online. The clinical data were analyzed using statistical and bioinformatic approaches. Results: A total of 31 genetically confirmed HTGTI patients were collected from our hospital and cases reported in the literature. The clinical manifestations showed the median age of onset was 6.0 (1.9,12.0) months. All the patients had normal psychiatric status, but 22.6% of them presented growth retardation and short stature, 93.5% had hepatomegaly, and 16.1% had splenomegaly. Only a few children were reported with jaundice, cholestasis and obesity (3.2%~ 6.5%). The laboratory investigations showed that 96.8% of them had hypertriglyceridemia (HTG) with a median level of 3.1 (2.1, 5.5) mmol/L, but only 30.0% had returned to normal during the fellow-up. 93.5% of patients had elevated ALT with an average level of 92.1±43.5 U/L, while 38.7% had hypercholesterolemia. Upon abdominal imaging, all patients presented fatty liver and liver steatosis, with 66.7% of patients showing hepatic fibrosis. Statistical differences in TG level were observed in 6mo group compared with the older groups, and in 13mo-6yr group with >6yr group (H = 22.02, P <0.05). The restricted cubic spline model showed severe HTG decreased in the early stage of infants to the normal level; however, it rebounded again to a mild or moderate level after the following days. The genetic test revealed that the main variant types of the GPD1 gene were missense variants (51.6%), followed by splicing variants (35.5%) and nonsense variants (12.9%). 87.1% of patients were homozygous variants, with the most frequent loci being c.361‐1G > C and c.895G > A. Conclusion: The common manifestations of HTGTI were HTG, hepatomegaly, elevated liver transaminases, hepatic steatosis in early infancy. However, the recurrence of aberrant HTG may pose long-term detrimental effects on HTGTI patients.